2012
DOI: 10.2337/dc11-1820
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Is Associated With Left Ventricular Diastolic Dysfunction in Patients With Type 2 Diabetes

Abstract: OBJECTIVEData on cardiac function in patients with nonalcoholic fatty liver disease (NAFLD) are limited and conflicting. We assessed whether NAFLD is associated with abnormalities in cardiac function in patients with type 2 diabetes.RESEARCH DESIGN AND METHODSWe studied 50 consecutive type 2 diabetic individuals without a history of ischemic heart disease, hepatic diseases, or excessive alcohol consumption, in whom NAFLD was diagnosed by ultrasonography. A tissue Doppler echocardiography with myocardial strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
2
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 35 publications
(62 reference statements)
8
116
2
4
Order By: Relevance
“…Interestingly, after correction for well-known cardiometabolic risk factors (gender, age, visceral obesity, IFG/diabetes and hypertension) severe fibrosis maintained its link not only with the parameters of cardiac geometry (left atrial volume, LVM/H 2.7 , PWT and RWT), but also with the indices of diastolic (lateral TDI e', E/e', E/A ratio) and systolic (EF) function. These results expand previous reports in small cohorts of NAFLD patients [10][11][12][13], reporting a significant impairment in cardiac structure and function, as assessed by echocardiography or MRI, in clinically diagnosed NAFLD patients compared with subjects without fatty liver. Along this line, our results fit with the evidence for an association between liver injury and intima-media thickness [2], another early cardiovascular alteration, also present in NAFLD patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, after correction for well-known cardiometabolic risk factors (gender, age, visceral obesity, IFG/diabetes and hypertension) severe fibrosis maintained its link not only with the parameters of cardiac geometry (left atrial volume, LVM/H 2.7 , PWT and RWT), but also with the indices of diastolic (lateral TDI e', E/e', E/A ratio) and systolic (EF) function. These results expand previous reports in small cohorts of NAFLD patients [10][11][12][13], reporting a significant impairment in cardiac structure and function, as assessed by echocardiography or MRI, in clinically diagnosed NAFLD patients compared with subjects without fatty liver. Along this line, our results fit with the evidence for an association between liver injury and intima-media thickness [2], another early cardiovascular alteration, also present in NAFLD patients.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, studies in small cohorts of subjects at high [10,11] or low [12] cardiometabolic risk highlighted the association of an ultrasonographic diagnosis of NAFLD, after adjustment for metabolic confounders, with a significant impairment in echocardiographic diastolic function compared to non-NAFLD cases. Along this line, a recent study on a small cohort of NAFLD patients reported significant changes in cardiac structure and function as assessed by MRI, in the absence of metabolic changes or overt cardiac disease [13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limited number of the included studies, the optimal dose and the duration of therapy were difficult to determine. In addition, IR is widely considered to be a pivotal feature of NAFLD, which is strongly and independently associated with the increased risk of type 2 diabetes (36,37). Although metformin has been used for the treatment of diabetes for >50 years, it has currently become one of the first-line treatment options in the management of diabetes, and is recommended by a number of international guidelines and consensus (38).…”
Section: A B C Dmentioning
confidence: 99%
“…Considering the influence of liver fat on metabolic health and the association of nonalcoholic fatty liver disease (NAFLD) with features of the metabolic syndrome 24 , others have looked at NAFLD patients and demonstrated subclinical myocardial systolic and diastolic dysfunction in the presence or absence of type 2 diabetes (T2DM) 25,26 .…”
Section: Introductionmentioning
confidence: 99%